Efek Seduhan Madu dan Jahe Terhadap Intensitas Emesis Gravidarum pada Ibu Hamil Trimester 1 - Devy Lestari Nurul Aulia; Arum Dwi Anjani; Sarmauli Franshisca Sihombing; Adelia Despriyanti; Vinda Rodiatul Hikmah (Lembaga Pengembangan Kinerja Dosen, 2024)
As a midwife must be able to provide midwifery care to overcome these complaints, one of the discomforts experienced by pregnant women is nausea and vomiting/emesis gravidarum. This study was conducted on pregnant women in the first trimester who experienced emesis gravidarum at the Fitri Medica Pratama Clinic in August - September 2024. A total of 35 people. Sampling in this study used the total sampling method. It is known that the average intensity of Emesis Gravidarum before being given Honey and Ginger Brewing was 11.14. It is known that the average intensity of Emesis Gravidarum after Honey and Ginger Brewing was 7.40. So it can be concluded that there is an effect of Honey and Ginger Brewing on the intensity of Emesis Gravidarum in Pregnant Women in the First Trimester with a p-value of 0.001 (p <0.05).